Evaluasi pola penggunaan obat dispepsia berdasarkan indikator WHO (World Health Organization) pada pasien rawat jalan Puskesmas Karang Taliwang tahun 2019 - Helen Nabila; Ni Made Amelia Ratnata Dewi; Ima Arum Lestarini (Sasambo Journal of Pharmacy, 2022)
Dyspepsia is a collection of several clinical symptoms consisting of pain in the pit of the stomach, flatulence, early satiety, nausea, and vomiting. The incidence of dyspepsia at the Karang Taliwang Public Health Center until 2019 was quite high. Evaluation of drug use at the Puskesmas has never been carried out, so it is necessary to know the pattern of use of dyspepsia drugs at the Karang Taliwang Public Health Center. This review aimed to determine the pattern of dyspepsia drug use in outpatient dyspepsia at Karang Taliwang Public Health Center using prescribing indicators developed by the World Health Organization. This study is a descriptive study of retrospective drug use. Sampling using a consecutive sampling method. Prescription data and medical records were collected through observation sheets. The results of the study on drug use patterns were the average number of drug items per sheet of 2.55 prescription; the percentage of drugs prescribed with generic names was 99,37%; the percentage of prescription drugs with antibiotics was 1.61%; the percentage of prescription drugs with injection preparations was 0%; and the percentage of drugs prescribed according to the Formularium was 96.84%.